Lipase-Catalyzed Ring-Opening Polymerization of β-Butyrolactone: End-Group Analysis of Poly(3-hydroxybutanoate) Using Supercritical Fluid Chromatography - Osanai, Yasushi; Toshima, Kazunobu; Matsumura, Shuichi (Macromolecular bioscience, 2001)
The ring‐opening polymerization of (R,S)‐β‐butyrolactone (BL) in bulk was analyzed with respect to the polymer structure of the resulting poly[(R,S)‐3‐hydroxybutanoate)] [P(3HB)] by isolation of the pure form using preparative supercritical CO2 fluid chromatography. It was confirmed that the four‐membered BL was polymerized in bulk by lipase to yield the corresponding cyclic, hydroxy‐ and crotonate‐terminated P(3HB)s. The relative ratios of the three types of polymers depended on the lipase concentration as well as on the monomer conversion. It was also confirmed that both cyclic and linear P(3HB) polymer species were subject to hydrolysis, and inter‐ and intramolecular transesterification by lipase to produce two series of polymers having linear and cyclic structures with higher and lower molecular weight. The formation of the cyclic P(3HB) iss regarded as the characteristic feature of the lipase‐catalyzed polymerization of BL.